PG22 Is the role of in-situ simulation for foundation year one doctors justified following paid internship as a result of the Covid-19 pandemic?. (10th November 2020) - Keshtkar, Fatemeh; Ellerton, Laura; Sharma, Anju; Parr, T; Shanahan, T; Mercer, Simon
Abstract : Introduction: Final year medical students are perceived to be ill-prepared for the challenges of a newly qualified doctor. Evidence supports the suspicion that mortality and morbidity is higher on the first Wednesday of August, the day of junior doctor change over in the United kingdom1. In-situ simulation is encouraged as a strategy to improve patient safety due to its high fidelity and evidence of improved organisational learning2, 3. For this reason our institute has provided a series of in-situ simulation scenarios for the foundation year one (FY1) doctors during their induction period. Following Covid-19 pandemic, final year medical students were encouraged to participate in paid apprenticeships. As a result, many students had prior experience and exposure to unwell patients before starting their placement as an FY1. The aim of this study was to identify whether in-situ simulation was felt to be useful and the paid apprenticeship affected confidence when compared to previous groups. Methodology: FY1 Doctors at our institution were invited to participate in a high-fidelity in-situ simulated scenario in a clinical area, followed by a debrief focusing on management of a deteriorating patient, severe sepsis, and non-technical skills. The study involved a pre and post-scenario questionnaire were demographic data, information on confidence and views on simulation as an educational modality and the perceived impact of the apprentice scheme were collected. The data from this cohort of newly qualified doctors was compared to previous cohorts from 2014–2019. Results: 39 candidates participated in this years study. There was a 100% response rate to both the pre and post scenario questionnaire. 78% of the candidates enrolled onto the apprenticeship scheme with the majority(1/3) of the cohort finding the scheme 'quite useful', 5% 'not useful' and over ¼ stating extremely useful. When assessing confidence in management of acutely unwell patients there was no significant difference between the 2 groups. All 39 candidates felt simulation was a useful learning tool and found the in-situ simulation a positive experience. 95% expressed improved confidence in managing an unwell patient following the session. Conclusion: In-situ simulation is a practical method for the detection of latent error and is used to reinforce learning4. This study shows that FY1 doctors regardless of whether or not they were involved in paid apprenticeship, felt simulation was an useful and felt more confident managing acutely unwell patients following the high fidelity in-situ simulation scenario. References: Sørensen, J.L., Østergaard, D., LeBlanc, V. et al. Design of simulation-based medical education and advantages and disadvantages of in situ simulation versus off-site simulation. BMC Med Educ 17, 20 ( 2017). https://doi.org/10.1186/s12909-016-0838-3 Jen MH, Bottle A, Majeed A, Bell D, Aylin P. Early in-hospital mortality following trainee doctors' first day at work. PLoS One. 2009;4(9):e7103. Published 2009. doi:10.1371/.0007103 Patterson MD, Geis GL, Falcone RA, et al. In situ simulation: detection of safety threats and teamwork training in a high risk emergency department. BMJ Quality & Safety 2013;22:468–477. Riley, W.; Lownik, E.; Parrotta, C.; RN, K.M.; Davis, S. Creating high reliability teams in healthcare through in situ simulation training. Adm. Sci 2011;1:14–31.